2011
DOI: 10.1097/pas.0b013e318216c112
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of PAX8 Expression in Human Epithelial Tumors

Abstract: PAX8 is a paired-box gene important in embryogenesis of the thyroid, Müllerian, and renal/upper urinary tracts, and expression of PAX8 has been previously described in carcinomas from each of these sites. However, a large study including a wide variety of epithelial neoplasms from multiple organ sites other than the thyroid, kidney, or Müllerian system has not been performed. The goal of this study was to evaluate the utility of PAX8 immunostaining based on the evaluation of a wide range of epithelial tumors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
332
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(363 citation statements)
references
References 45 publications
21
332
1
1
Order By: Relevance
“…PAX8 is a transcription factor that is commonly expressed in epithelial tumors of the thyroid gland, parathyroid gland, kidneys and Mü llerian tract. 24,[32][33][34] In addition, PAX8 has recently also been described to label neoplastic epithelial cells of thymic epithelial neoplasms. 35 Interestingly, PAX8 expression has also been described in a subset of neuroendocrine neoplasms, such as pancreatic neuroendocrine tumors as well as duodenal and rectal carcinoid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PAX8 is a transcription factor that is commonly expressed in epithelial tumors of the thyroid gland, parathyroid gland, kidneys and Mü llerian tract. 24,[32][33][34] In addition, PAX8 has recently also been described to label neoplastic epithelial cells of thymic epithelial neoplasms. 35 Interestingly, PAX8 expression has also been described in a subset of neuroendocrine neoplasms, such as pancreatic neuroendocrine tumors as well as duodenal and rectal carcinoid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that PAX8 positivity ranges from 97% to 100% in AIS and 0% to 87% in ECA. [1][2][3][4][5][6][7][8][9] The discrepancies among various studies may be attributable to several factors; the first is small sample size. Our study included 43 ECA (combined 2 cohorts) and 16 AIS, and is one of the largest studies.…”
Section: Comparison Of Pax8 Expression In Eca Versus Uterine Endometrmentioning
confidence: 99%
“…2 Furthermore, PAX8 was expressed in 97% to 100% of adenocarcinoma in situ (AIS) and in 0% to 87% of endocervical adenocarcinoma (ECA) specimens (summarized in Table 1). 1,[3][4][5][6][7][8][9] The goal of this study was to evaluate PAX8 expression by immunohistochemistry (IHC) in endocervix.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] PAX8 has been reported to have a role in diagnosis as a sensitive and specific marker for tumors of renal, Mü llerian or thyroid origin in both primary and metastatic sites. [8][9][10][11] Others have reported PAX8 expression in B-lymphocytes in both normal lymphoid organs and hematological neoplasms as well, 8,10,11 and lymphocytes have been used as an internal positive control for PAX8 immunostaining. 10,12 PAX5 by contrast, regulates B-cell development and influences the balance between immunoglobulin secretion and B-cell proliferation.…”
mentioning
confidence: 99%
“…[8][9][10][11] Others have reported PAX8 expression in B-lymphocytes in both normal lymphoid organs and hematological neoplasms as well, 8,10,11 and lymphocytes have been used as an internal positive control for PAX8 immunostaining. 10,12 PAX5 by contrast, regulates B-cell development and influences the balance between immunoglobulin secretion and B-cell proliferation. PAX5 expression is a wellknown immunohistochemical marker for defining B-cell lineage in hematological neoplasms.…”
mentioning
confidence: 99%